The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.cub.2014.05.070
|View full text |Cite
|
Sign up to set email alerts
|

The Alarming Decline of Mediterranean Fish Stocks

Abstract: In recent years, fisheries management has succeeded in stabilizing and even improving the state of many global fisheries resources [1-5]. This is particularly evident in areas where stocks are exploited in compliance with scientific advice and strong institutional structures are in place [1, 5]. In Europe, the well-managed northeast (NE) Atlantic fish stocks have been recovering in response to decreasing fishing pressure over the past decade [3-6], albeit with a long way to go for a universal stock rebuild [3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
214
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(241 citation statements)
references
References 26 publications
18
214
2
2
Order By: Relevance
“…On the other hand, Mediterranean stocks have largely declined in the last 15 years and their exploitation level has raised or remained above the F MSY level during the same period of time (Vasilakopoulos et al, 2014; this paper). Here we showed that up to 2014, the average exploitation rate for the main demersal and small pelagic stocks of the Mediterranean Sea is around three times the estimated level of F MSY , with a general similar pattern across species and area, which confirms analyses recently conducted (STECF, 2015c).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…On the other hand, Mediterranean stocks have largely declined in the last 15 years and their exploitation level has raised or remained above the F MSY level during the same period of time (Vasilakopoulos et al, 2014; this paper). Here we showed that up to 2014, the average exploitation rate for the main demersal and small pelagic stocks of the Mediterranean Sea is around three times the estimated level of F MSY , with a general similar pattern across species and area, which confirms analyses recently conducted (STECF, 2015c).…”
Section: Discussionmentioning
confidence: 74%
“…In recent years European fisheries managers have witnessed the success of the European CFP in the north (i.e., North East Atlantic, Cardinale et al, 2012;Fernandes and Cook, 2013) and at the same time, its failure in the south (i.e., Mediterranean Sea, Colloca et al, 2013;Vasilakopoulos et al, 2014). Thus, despite the fact that both areas are managed under the same broad fishery policy (i.e., European CFP), a large discrepancy in management performance still occur between the North East Atlantic and the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations